Figural creativity of dyslexic and non-dyslexic in indonesia children sample - Wanawir AM, Wanawir AM; Kurniati, Lisdwiana; Saikhoni, Saikhoni (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Children who have difficulties in writing and reading are called dyslexia. This disorder is caused by neurobiologis disorder that bring a problem in language cognitive domain, however some research states that dyslexic children often have better other cognitive domain abilities than children in general, for instance, intelligence level, talent, and etcetera. That is why the researcher compares figural creativity level of dyslexic children and non-dyslexic children. Figural creativity is applied because dyslexic children undergone problem in language thus they do not use verbal creativity. This study employed ex post facto research design and the subject were 8 students that consisted of 4 dyslexic children and 4 non-dyslexic children. Caloured Progressive Matric test was used to measure creativity level. The result shows that there is no differences between creativity level of dyslexic students and non- dyslexic students. It can be seen when children have similar average intelligence, they have the same average level of creativity. It also supported by creativity theories which states that creativity is formed by individual cognitive factor.